The Impact of Global Transformations of the Business Environment on the Development of Enterprises - Karlova Olena A. (Bìznes Inform)
In the context of rapid technological progress, globalization of markets, changing economic and political conditions, as well as increasing environmental challenges, enterprises face the need for constant adaptation and innovation. The aim of the article is to study the impact of global transformations of the business environment on the development of enterprises. The article considers the types of global transformations, which include globalization and the technological, economic, social, environmental, political transformations. The theoretical foundations of globalization, technological changes, economic fluctuations, socio-demographic and environmental challenges, as well as political instability are considered. The factors influencing global transformations are studied, among which technological progress, international trade and investment, changes in consumer preferences, socio-demographic changes, environmental challenges and political instability are allocated. It is identified that global transformations not only create new opportunities for the growth and development of economic entities, but also pose significant risks and challenges. Understanding how to overcome these changes is becoming key factor to ensuring business resilience and competitiveness. The aspects of the impact of global transformations of the business environment on the development of enterprises are analyzed. Both positive and negative aspects of global transformations for business are identified, including the expansion of sales markets, access to advanced technologies and investments, increased competition and dependence on external factors. Thus, in order to thrive in the context of globalization, enterprises must adopt a strategic approach, be flexible, introduce innovations and effectively manage risks. It is necessary to actively implement advanced technologies, adapt to consumer needs, take into account environmental and social factors in its activities and be ready for changes in the political and economic situation.